The Influence of Muslim Religiosity on Waqf Participation: A Meta-Analysis of Factors and Trends (2014–2024) - Moh Agus Nugroho; Suci Larasati; Md Mahfujur Rahman (UIN Kiai Haji Achmad Siddiq Jember, 2024)
This study analyzes the relationship between religiosity and Muslim participation in waqf through a meta-analysis of 20 studies from 2014–2024. This study is important because although religiosity is considered to influence philanthropy, previous research results have shown significant variations in effects and context. This study fills the gap by evaluating these variations, including regional, cultural, and methodological factors. The study focuses on the extent to which religiosity influences waqf participation. Data were collected from quantitative articles based on Scopus, using JASP software for effect size analysis, heterogeneity, and visualization through forest and funnel plots. The results show a moderate positive effect of religiosity on waqf participation (effect size 0.23) but with high heterogeneity (I² = 96.55%), indicating significant variation between studies. The findings identify contextual factors such as socio-cultural differences, religious practices, and methodological variations as key determinants. The study concludes that waqf promotion strategies must adjust to regional and cultural contexts for greater effectiveness. Recommendations include further cross-cultural research and the development of context-based approaches to reduce heterogeneity. These findings guide policymakers and waqf institutions in designing effective religiosity-based strategies.